Writing a research protocol in pediatric oncology - Gamboa, Maryelle Moreira Lima; Gregianin, Lauro (Clinical and Biomedical Research, 2013)
Children are considered an especially vulnerable population in a clinical trial. Specific regulations of research in pediatrics are focused upon protection from potential risks. Clinical trials in oncology have become an important step to the researchers to discover new drugs, new combinations of known drugs and new methodologies. The aim of this manuscript is to help the starter researchers to elaborate pediatrics oncology protocols for clinical trials. This guide describes the relevant aspects before writing a research protocol and a template of research protocol. Moreover, it shows the importance of a well-designed research protocol and its attachments - informed consent and assent forms – in a pediatric oncology study.